MOOSE ANTLER MORPHOLOGY AND ASYMMETRY ON ISLE ROYALE NATIONAL PARK - Mills, Kenneth J.; Peterson, Rolf O. (Lakehead University, 2013)
Isle Royale National Park, an island archipelago in Lake Superior, supports moose at higher density (1–4/km2) relative to most other North American sites. We compared antler size and asymmetry measurements from Isle Royale moose that died of natural causes to measurements available for other regional moose populations in published literature. We used these comparisons to test predictions that antlers of Isle Royale moose would be smaller and more asymmetric than other regional populations due to the high population density and the resulting ecological conditions on Isle Royale. Moose on Isle Royale follow the same patterns of antler development as elsewhere, reaching maximum size at 7–8 years of age with slight declines after age 10–12. However, these moose develop antlers that are much smaller than all measured North American subpopulations. Antler size was most comparable to moose from Scandinavia where moose exist at comparably high population density. Boone and Crockett score, which is commonly used to compare antler size, performed poorly at ranking individuals with large antlers suggesting that more biologically relevant measures such as antler volume should be considered for comparisons of antler size. Pedicle constriction was found to be a reliable indicator of senescence among old bulls. Antler asymmetry was negatively related to antler size and was more extreme than asymmetry measured in Alaskan moose. Moose age had no detectable effect on the degree of antler asymmetry. In general, bull moose on Isle Royale develop smaller, more asymmetric antlers than other North American subpopulations which exist at lower density, consistent with the hypothesis that these qualities are related to nutrient limitation caused by high population density. Results, however, may also reflect genetic differences and artifacts of sampling.